Parental occupational exposure to pesticides and risk of childhood cancer in Switzerland: A census-based cohort study - Coste, A.; Bailey, Helen; Kartal-Kaess, M.; Renella, R.; Berthet, A.; Spycher, B.D. (BMC, 2020)
Background: Pesticide exposure is a suspected risk factor for childhood cancer. We investigated the risk of developing childhood cancer in relation to parental occupational exposure to pesticides in Switzerland for the period 1990-2015.